Funding liquidity and bank risk taking - Khan, Muhammad Saifuddin; Scheule, Harald; Wu, Eliza (Journal of Banking & Finance, 2017)
This study examines the relationship between funding liquidity and bank risk taking. Using quarterly data for U.S. bank holding companies from 1986 to 2014, we find evidence that banks having lower funding liquidity risk as proxied by higher deposit ratios, take more risk. A reduction in banks’ funding liquidity risk increases bank risk as evidenced by higher risk-weighted assets, greater liquidity creation and lower Z-scores. However, our results show that bank size and capital buffers usually limit banks from taking more risk when they have lower funding liquidity risk. Moreover, during the Global Financial Crisis banks with lower funding liquidity risk took less risk. The findings of this study have implications for bank regulators advocating greater liquidity and capital requirements for banks under Basel III.